A formação litúrgica no Brasil a partir da Sacrosanctum Concilium - Leão, Fábio de Souza (2010)
This thesis written by Fabio de Souza Leão has as title: The liturgical formation in Brazil from Sacrosanctum Concilium. The main objective of this research is to analyze, although in general, why the catholic communities in Brazil did not find a satisfactory way in the liturgy, the source of their spirituality, even after the renewal of council with the promulgation of the constitution on the liturgy in 1963. This scientific research is justified by the deficiency of liturgical formation of the brazilian clergy even after the Second Vatican Council. The changes in the liturgy could not produce the expected results, in other words, a spiritual renovation of the liturgy in the minds and hearts of the priests. Many times they understood the liturgical constitution more like reform that renovation, a much more comprehensive aspect than reformer, because it requires a new style of liturgical life able to promote the active, full, conscious, fruitful and pious participation, which are requirements of own essence of liturgy. The primary hypothesis of this research indicates that the liturgical formation of clergy as vertex of problem in active participation in communities is deficient. His nonassimilation of the renewed liturgy affects communities, and this has direct involvement in the pastoral of the church.The theoretical research, a method followed in this work, comes to important results for the Church in Brazil: the priests are not yet imbued with the spirit and strength of the liturgy and its theological-liturgical training is weak, they had not caught the spirit of the liturgical renovation and many of them still remain on the periphery of the cult of the Christian mystery. They are bounded on liturgical rules, devotionals and celebrationshow; it misses initiation in the liturgical life and a better organization for an effective liturgical formation at the parish level